SUSTAINABLE DEVELOPMENT OF SINGLE-INDUSTRY TOWNS AS A FACTOR OF ECONOMIC STABILIZATION - А. Nurgalieva; М. Karimbergenova; L.Moldashbayeva; L. Kashuk; A. Soltangazinov; K.Jrauova (Academic Journal of Physical and Chemical Sciences, 2019)
The article highlights the issues of increasing the efficiency of socio-economic development of single-industry towns of strategic importance. Modern economic systems are built on the principles of territorial distribution and concentration, with a special economic role is assigned not only to metropolitan areas, large and medium-sized cities, but also small urban areas with adjacent territories. In the practice of the economy of the Republic of Kazakhstan, many of the small cities have a single-industry economic structure over a long period of time. The authors of the study took the Aksumonotown as a basis.The industry of such cities is characterized by a low level of technological development, development of small and medium-sized businesses, and demographic attraction. As a result, the economic systems of small cities and adjacent territorial districts demonstrate low competitiveness. At the same time, world practice shows and demonstrates examples of successful solution of the socio-economic problems of small cities and territories. The article presents a solution to the problem of controlled impact on the development of the economy of a single-industry city at the expense of small and medium-sized businesses through the use of an economic model that includes a number of interrelated organizational elements.